The Importance of the Public Global Parameter on Ring-LWE problem-based Key Encapsulation Mechanims - Villena, Reynaldo C.; Terada, Routo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2022)
There are cryptographic systems that are secure against attacks by both quantum and classical computers. Some of these cryptographic systems are the Key Encapsulation Mechanisms (KEM) based on Ring-LWE problem. Some Ring-LWE problem-based KEMs include a public global parameter that is random and uniformly chosen. This parameter is used to generatea public key using in the process one secret key. In this work, we analyze some values of the public global parameter that leak information about the secret key.